Difficulties of Teaching Social Studies in the Absence of Educational Resources - Teachers' Perspective in Third Cycle of Basic Education in Independent Zakho Administration - Nida Fattah (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aimed to identify the difficulties of teaching social studies in the absence of educational resources from the perspective of teachers in the third cycle of basic education in Independent Zakho Administration according to the following variables: gender, years of teaching experience, academic qualification, and grade level. The study sample included 94 male and female social studies teachers from Grades 7-9. A questionnaire consisting of 28 items distributed across five dimensions was developed based on relevant literature and distributed to the research sample during November 2025. The study found statistically significant differences at the 0.05 level between the means of sample responses according to gender, years of experience, and academic qualification variables, indicating that the absence of educational resources significantly impacts teaching effectiveness differently based on these demographic factors. However, no statistically significant differences were found regarding the grade level taught. Based on these findings, the researcher recommended several measures, most importantly the need for educational authorities to provide adequate educational resources, establish resource centers in schools, allocate sufficient budgets for teaching materials, and develop partnerships with organizations to support resource provision.